2009
DOI: 10.1016/j.envres.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to PCDDs/PCDFs and dioxin-like PCBs in relation to birth weight

Abstract: Several human studies have shown that low-level exposure to environmental contaminants, such as polychlorinated biphenyls (PCBs) and organochlorine pesticides, negatively influences birth outcomes.However, the effects of low-level exposure to polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and dioxin-like PCBs (DL-PCBs) on birth outcomes have not been clarified in human studies.A prospective cohort study was established to investigate the possible adverse effects of PCDDs/PCDF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 43 publications
4
57
2
Order By: Relevance
“…This is in line with other studies with comparable exposure levels that have reported negative effects of dioxin-like chemicals on birth weight (Patandin et al 1998, Tajimi et al 2005, Konishi et al 2009). All: precise age at examination (gestational ageCexamination age for 0 and 3 months).…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with other studies with comparable exposure levels that have reported negative effects of dioxin-like chemicals on birth weight (Patandin et al 1998, Tajimi et al 2005, Konishi et al 2009). All: precise age at examination (gestational ageCexamination age for 0 and 3 months).…”
Section: Discussionsupporting
confidence: 81%
“…Pesticides have been linked to cancer, birth defects, and damage to the nervous system, and the functioning of the endocrine systems [16]. Other research showed a link between pesticide exposure and adverse effects on children and fetuses such as low birth weight [17,18], preterm birth or toxemia [19], stillborn infants [20] and miscarriages [21]. In China's Anhui province, DDT was associated with miscarriages in the first few weeks of pregnancy [22].…”
Section: Discussionmentioning
confidence: 99%
“…While few reports on the possible effects of POP exposure on fetal growth have been published to date, some evidence suggests that prenatal exposure to these compounds could be associated with disturbed hormone levels during pregnancy [34-36]. Prenatal exposure to PCBs has been related to lower birth weight, decreased thyroid function, and modification of the sex ratio at birth [37, 38]. In another study in the same population of the present work, it was pointed out that PBDEs may impair fetal growth in late pregnancy and reduce birth size [39].…”
Section: Discussionmentioning
confidence: 99%